1995
DOI: 10.1111/j.1464-410x.1995.tb07226.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostate‐specific antigen obtained under optimal conditions determines extracapsular adenocarcinoma of the prostate

Abstract: These data demonstrate that optimal serum PSA values correlate well with pathological stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…However, they also reported that the presence of organ-confined disease in patients with a borderline serum PSA level of 4–10 ng/ml and clinical stage T 2a to T 2c varied widely (22–83%). Ehreth et al [8] studied 207 patients with clinically organ-confined prostate cancer and found that a PSA value of less than 4 accurately predicted organ-confined disease in 42 of 51 patients (82%). In contrast, extracapsular disease was present in 74 of 84 patients (88%) who had a PSA value of more than 10.…”
Section: Introductionmentioning
confidence: 99%
“…However, they also reported that the presence of organ-confined disease in patients with a borderline serum PSA level of 4–10 ng/ml and clinical stage T 2a to T 2c varied widely (22–83%). Ehreth et al [8] studied 207 patients with clinically organ-confined prostate cancer and found that a PSA value of less than 4 accurately predicted organ-confined disease in 42 of 51 patients (82%). In contrast, extracapsular disease was present in 74 of 84 patients (88%) who had a PSA value of more than 10.…”
Section: Introductionmentioning
confidence: 99%
“…The PSA value has been known to generally be correlated with the cancer volume, GS, ECE, and the occurrence of lymph node metastases. For example, one study showed that a PSA level > 10 ng/mL has a sensitivity, specificity, and PPV of 61%, 88%, and 88% for the detection of ECE, respectively 17. Narayan, et al established probability plots that can predict the presence of ECE, seminal vesicle involvement, and lymph node metastases using PSA level 18.…”
Section: Discussionmentioning
confidence: 99%
“…; der positive Vorhersagewert für ein intrakapsuläres Stadium beträgt für PSA < 4ng/ml 82,4%[1], Andererseits ist der Nutzen der Früherkennung aber nicht bewiesen. Entgegen der von Scardino in der Washington Post[9] gemachten Äußerung "only good Cancer is a dead Cancer" ließ sich die Mortalität trotz durchschnittlich 5 Jahre früher einsetzender Therapie nicht verringern bzw.…”
unclassified